Adaptive planning: a proposal to manage nanotechnology projects - Marcella Rocha Franco; Glaura Goulart Silva; Raoni Barros Bagno; Jonathan Sim\~oes Freitas (Innovation & Management Review, 2025)
Purpose Research, development and innovation (RD&I) projects involving nanotechnology are complex, requiring an agile mindset and approaches capable of adapting to new discoveries, yet alternative project management (PM) approaches are still mainly limited to software development. This study aims to fill part of this gap by developing and evaluating the use of an adaptive planning model to contribute to PM in nanotechnology. Design/methodology/approach The approaches of 'process tracing' and complexity dimensions were combined in an in-depth case study to identify events and build a real-time map of the complexities of a collaborative RD&I project involving nanotechnology, prominent in the national context. Findings The systematization of the case in question resulted in the proposal of an adaptive and replicable model with implementation guidelines capable of contributing in real time to managers' understanding of complexities and decision-making in complex projects. Research limitations/implications This study's limitations included the limited number of informants and the focus on a single case. However, this can serve as a starting point for further investigation aiming to advance the application of adaptive approaches to PM in RD&I projects involving nanotechnology. Originality/value The study fills a knowledge gap in the field of adaptive planning for environments beyond software development and creates an opportunity for discussions on PM approaches in hard science contexts.
Keywords: 650; Adaptive planning; Complex RD&I projects; Nanotechnology